2009
DOI: 10.1002/jssc.200900460
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of dispersive liquid–liquid microextraction of Co(II) and Fe(III) as their oxinate chelates and analysis by HPLC: Application for the simultaneous determination of Co(II) and Fe(III) in water samples

Abstract: In this study, dispersive liquid-liquid microextraction method was used for the preconcentration and simultaneous determination of Co(II) and Fe(III) in water samples as their oxinate chelates. In dispersive liquid-liquid microextraction process, methanol and chloroform were used as disperser and extracting solvents, respectively, and the ligand 8-hydroxy quinoline was used as a chelating agent for the extraction of Co(II) and Fe(III). HPLC was applied for the quantitation of the analytes after preconcentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 62 publications
0
16
0
1
Order By: Relevance
“…Figure 7 shows a chromatogram taken for BCR 715 wastewater-SRM, by the HPLC-DAD. (Zhang et al 2005;Chung and Chung 2003;Peng et al 2005;Zhu et al 2007;Arain et al 2009;Amoli et al 2006;Farajzadeh et al 2010;Cheng et al 2008) was shown in Table 3. The limit of detection (LOD) for Co(II) is better than those of the direct HPLC measurements reported in the previous similar papers, also better than those of a combination of preconcentration and HPLC, required laborious and complicated sample preparation steps.…”
Section: Analysis Of Water Samplesmentioning
confidence: 90%
“…Figure 7 shows a chromatogram taken for BCR 715 wastewater-SRM, by the HPLC-DAD. (Zhang et al 2005;Chung and Chung 2003;Peng et al 2005;Zhu et al 2007;Arain et al 2009;Amoli et al 2006;Farajzadeh et al 2010;Cheng et al 2008) was shown in Table 3. The limit of detection (LOD) for Co(II) is better than those of the direct HPLC measurements reported in the previous similar papers, also better than those of a combination of preconcentration and HPLC, required laborious and complicated sample preparation steps.…”
Section: Analysis Of Water Samplesmentioning
confidence: 90%
“…A DLLME method was presented by Farajzadeh et al [177] for the preconcentration of cobalt and iron ions prior to their determination by HPLC-UV technique. HPLC is a simple and relatively cheap technique that is needed for the samples at microlitre volumes.…”
Section: 36mentioning
confidence: 99%
“…Quinolin-8-ol mostly binds to metal ions in a bidentate fashion (Bernhardt & Lawrance, 2004). It has attracted interest in industrial applications, showing potential as an extracting agent for metal ions in dilute solutions (Farajzadeh et al, 2009). The bidentate ligand quinolin-8-ol can complex to a variety of metal ions, either as a neutral molecule or, more commonly, as a deprotonated anion with the loss of the hydroxy H atom (Maiti et al, 2005;Colquhoun et al, 2002;Xiang et al, 2011).…”
Section: Introductionmentioning
confidence: 98%